My Village Is Dying? Integrating Methods from the Inside Out. (5th July 2018) - Peters, Paul; Carson, Dean; Porter, Robert; Vuin, Ana; Carson, Doris; Ensign, Prescott
Abstract: The purpose of this paper is to confront the notion of "decline" at the village level by illustrating a more immersive approach to sociological and demographic research within rural and remote communities. The research uses case studies of three villages in Australia, Canada, and Sweden, all of which have been labeled as "declining villages, " typified by population loss, an aging population, high rates of youth outmigration, and loss of businesses and services. This paper argues that focusing solely on quantitative indicators of demographic change provides a narrow view of rural village trajectories and ignores subtle processes of local adaptation that are hidden from quantitative data sets. Our research integrates quantitative data from the "outside" with qualitative data from the "inside, " including visual ethnography, to develop a more balanced perspective on how villages have been changing and what change could mean locally. These objectives are accomplished by revisiting a Dirt Research methodology applicable to a broad range of research into rural and remote villages. Résumé: Le but de cet article est de confronter la notion de "déclin" au niveau d'un village en illustrant une approche sociologique et démographique plus immersive dans le cadre de communautés rurales et éloignées. La recherche utilise les études de cas de trois villages en Australie, au Canada et en Suède, tout considérés comme des "villages en déclin, " caractérisés par des pertes de population, une population vieillissante, et des taux élevés d'émigration des jeunes, ainsi que la perte d'entreprises et de services. Cet article prétend qu'une emphase sur des indicateurs seulement quantitatifs et des changements démographiques donne une vision réductrice des trajectoires des villages et ignore des processus subtils d'adaptation locale qui sont masqués par des données quantitatives. Notre recherche intègre des données quantitatives "externes" avec des données qualitatives "internes, " incluant l'ethnographie visuelle, afin de développer une perspective plus équilibrée montrant comment ces villages ont changé et ce que le changement peut signifier localement. Ces objectifs sont réalisés en revisitant une méthodologie 'Dirt research' applicable à un éventail large de recherche sur les villages ruraux et éloignés.